Characteristics of Alumina‐Based Inclusions in Low Carbon Al‐Killed Steel under No‐Stirring Condition. Issue 9 (7th March 2013) - Yang, Wen; Wang, Xinhua; Zhang, Lifeng; Wang, Wanjun
Abstract Alumina‐based inclusions have a detrimental effect on castability and the surface quality of the LCAK steel sheet, thus they are expected to be removed from the steel. In order to get the detailed transient characteristics of inclusion aggregation and removal after Al addition, laboratory experiments were performed to study the formation of alumina inclusions during Al‐killed process of low carbon steel at 1873 K under no‐stirring condition. The characteristics of the alumina‐based inclusions in terms of amount, size, and morphology were investigated. The results showed that the evolution of the AF (area fraction) and average size of Al2O3 inclusions after deoxidation was divided into three stages: 0–9 min, aggregation was dominant; 9–22 min, floating was dominant; after 22 min, both the AF and size decreased slowly. Accordingly, the stirring was suggested to be strengthened in the initial 9 min under stirring condition to promote the removal of large inclusions. Based on the correlation between inclusion morphology and holding time, a simple precipitation and growth mechanism of alumina inclusions was proposed, which consisted of three main stages: precipitation stage of Al2O3 single particles, aggregation stage, and sintering stage of aggregated inclusions. And it was implied that the Ostwald‐Ripening can be finished up within 20 min.